Phyto-fabricated Pd@Ag bimetallic nanocomposites using carica papaya leaf extract: A dual-functional platform for catalysis and antimicrobial defence - Jayamani T; A. Elakkiya Devi; T. Augustine Arul Prasad; B. Scholastica Mary Vithiya; Lawrance Richardson (Current Research in Green and Sustainable Chemistry, 2025)
This study presents a green synthesis approach for bimetallic palladium–silver (Pd@Ag) nanocomposites using Carica papaya leaf extract, aimed at addressing urgent environmental and biomedical challenges. The synthesized Pd@Ag nanoparticles exhibited remarkable catalytic efficiency in degrading hazardous organic dyes, achieving 82 % and 88 % reduction of Congo Red and Methylene Blue, respectively, within minutes in the presence of NaBH4. This highlights their strong potential in wastewater treatment and environmental detoxification. Furthermore, the Pd@Ag nanocomposites demonstrated broad-spectrum antimicrobial activity, showing significant zones of inhibition against major bacterial pathogens including Escherichia coli and Staphylococcus aureus, as well as antifungal effects against Candida albicans and Aspergillus niger. The dual functionality—efficient catalysis and potent antimicrobial defence—establishes these green-synthesized nanoparticles as promising candidates for sustainable environmental and biomedical applications.